Establishing Standards for Trauma Nursing Education: The Central Ohio Trauma System's Approach. Issue 1 (January 2017) - Haley, Kathy; Martin, Stacey; Kilgore, Jane; Lang, Carrie; Rozzell, Monica; Coffey, Carla; Eley, Scott; Light, Andrea; Hubartt, Jeff; Kovach, Sherri; Deppe, Sharon
Abstract : Trauma nursing requires mastering a highly specialized body of knowledge. Expert nursing care is expected to be offered throughout the hospital continuum, yet identifying the necessary broad-based objectives for nurses working within this continuum has often been difficult to define. Trauma nurse leaders and educators from 7 central and southeastern Ohio trauma centers and 1 regional trauma organization convened to establish an approach to standardizing trauma nursing education from a regional perspective. Forty-two trauma nursing educational objectives were identified. The Delphi method was used to narrow the list to 3 learning objectives to serve as the framework for a regional trauma nursing education guideline. Although numerous trauma nursing educational needs were identified across the continuum of care, a lack of clearly defined standards exists. Recognizing and understanding the educational preparation and defined standards required for nurses providing optimal trauma care are vital for a positive impact on patient outcomes. This regional trauma nursing education guideline is a novel model and can be used to assist trauma care leaders in standardizing trauma education within their hospital, region, or state. The use of this model may also lead to the identification of gaps within trauma educational systems.